Art and Entanglement in Strange Tools - Noë, Alva (Phenomenology and Mind, 2018)
What is art? Why does it matter? What does it tell us about ourselves? In this essay, I introduce and in some cases extend the basic account of these matters offered in Strange Tools (New York, Hill and Wang: 2016).